Analisis Efisiensi Termal Sebelum dan Sesudah Overhaul Turbin Inspection Di PLTGU Blok 3 Unit 2 PT PLN Nusantara Power UP Gresik - Muhammad Naufal Hardiansyah; Muhammad Ridwan (Universitas Muhammadiyah Metro, 2026)
This study analyzes the thermal efficiency performance of a Combined Cycle Power Plant (PLTGU) at PT PLN Nusantara Power, Gresik Generation Unit, focusing on Gas Turbine GT 3.2 in Block 3 Unit 2. The objective is to compare turbine performance before and after an overhaul (Turbine Inspection/TI). The research is driven by increasing electricity demand and the gradual degradation of gas turbine components due to operating hours, such as fouling and mechanical wear, which can increase fuel consumption and reduce efficiency. Thermal efficiency, based on the Brayton cycle theory, is used as the main performance indicator and is defined as the ratio of net work output to heat input (Qin). This research applies a field study method with a comparative before–after approach using actual operational data. The analyzed parameters include temperature, pressure, fuel flow rate, and lower heating value (LHV) at loads of 100 MW and 103 MW. Data processing and calculations were performed using Microsoft Excel. The results indicate that thermal efficiency improved after the overhaul. At 100 MW, efficiency increased from 30.5450% to 31.4085%, while at 103 MW it rose from 30.7662% to 31.4256%. Turbine output power also increased by 4.7 MW (4.55%). Overall, the overhaul positively restored turbine performance and improved thermal efficiency.